HEALTH COUNSELING HEALTH STARTS WITH FOOD AND HEALTHY SNACKS: HOW TO CHOOSE HEALTHY FOOD AND HEALTHY SNACKS: PENYULUHAN KESEHATAN TERHADAP KESEHATAN TUBUH BERAWAL DARI MAKANAN DAN JAJANAN YANG SEHAT: CARA MEMILIH MAKANAN DAN JAJANAN YANG SEHAT - Cut Suraiya Wahyuni Utami; Resmila Dewi; Rina Kurniaty; Erda Marniza (PT. ROCE WISDOM ACEH, 2024)
In order to achieve good health, it is necessary to apply healthy behavior in everyday life. These health behaviors include maintaining and improving health, protecting oneself from the threat of disease and participating in health empowerment activities. One of the behaviors that need to be considered is the behavior in applying the health of food consumed in everyday life, especially in children who are in elementary school. This Community Service activity was carried out on May 11, 2024 which took place in the Hall of SDN 5 Setui Banda Aceh, SD Nurul Fikri and MIN Tungkop. The methods used were lectures, questions and answers and discussions. It is hoped that the results of this counseling activity can be useful and continued with the application in the daily lives of participants who take part in this counseling.